PARTISIPASI ANGGOTA KARANG TARUNA SOTE PAGE DALAM PEMBANGUNAN MASYARAKAT DI DESA ANIK DINGIR KECAMATAN MENYUKE - Kristiana, Eplonia; Supriadi, Supriadi; Ramadhan, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the participation Youth Organization Sote Page members in Community Development in anik Dingir Village, Menyuke District. The research method used is descriptive with a form of qualitative research. Data collection techniques used were observation, interviews and documentation. The results of the study showed that, 1) The form of thinking in community development in Anik Dingir Village was already active as at the time of the Youth Organization work program Sote Page members discussed about providing education to people who are illiterate especially reading and writing and providing additional tutoring for children Elementary school. 2) The form of material in community development in Anik Dingir Village has been active such as giving donations of goods in the form of rice and boards. 3) The form of energy in community development in Anik Dingir Village is already active such as the activity of mutual cooperation in cleaning up water dams and repairing broken pipes. Keywords : Community Development, Participation, Youth Organization.